Space and Anthropology of Limit: A Philosophical Perspective - Pirni, Alberto (Frontiers in Astronomy and Space Sciences, 2016)
In no other living species does technology (or more precisely the need for technological development) play such an important role as it does in the human species. Almost every animal species is able to implement “techniques” in order to improve its living conditions, that is to produce tools or structures capable of enhancing its ability to procure food and defend itself. No animal, however, to the same extent as the human being, seems unable to do without the constant innovation of its own capacities and their outcomes. This is a constant factor, which unequivocally connotes our being human. It is a constant that we can say is expression of an essentially dual nature: fear of inadequacy, on the one hand, anxiety for perfection, on the other. This rationale remains surely a matter of fact regarding the “traditional” or “common” condition of the man, understood as a being living on the Earth with a specific biological structure. However, any possible understanding of the same issue requires new efforts if and as far we try to maintain it open in a totally different context: “the space”, namely, a not-specific place outside Earth in which the man is trying to give shape to a new path of its own surviving (§ 1). Here rises what we would like to call the "anthropology of limit". In order to grasp a provisional content for such expression, we must proceed “analytically”, first, by reconsidering briefly the two conceptual sides implied in that expression, namely “What is a man?” and “What do we mean with limit?” (§ 2). Secondly, we should try to reconsider the twofold results under a “synthetical” or comprehensive point of view, trying to gather a common area of questioning that opens up if and as far we shift and reconsider both conceptual sides of that expression within the “space-context” (§ 3).